CONTEXT BASED ANALYSIS IN THE TRANSFORMATION OF RENDRA'S POETRY MUSICALIZATION - Muhammad Fikri; Tomi Arianto; Karmila Alam Syah Wellem; Khairunnisa Khairunnisa (Asosiasi dosen IDEBAHASA KEPRI, 2023)
Poetry holds a very deep meaning that cannot even be only touched by a heuristic approach reading. When poetry is transformed into strings of tones or musicalization, the power of meaning in words will be even more stunning and make the affirmation of words stronger and more rooted. This article will reveal two of Rendra's transformation poems in the form of musicalized poems entitled “Serenada Kelabu” and “Kangen”. This article revealed the negation of